Perception towards Online and Face to Face Learning - Chhetri, Deb Bahadur (Scholars' Journal, 2022)
The COVID-19 pandemic scenario suspended educational activities. The traditional face-to-face educational model was replaced by an online one. The online mode of instruction has been adopted by higher education institutions. The direct conversation was broken off. To understand the justification for continuing the online method in higher education in the context of Nepal, it is reasonable to examine how both students and teachers feel about face-to-face learning that is done online. For the present study mixed method study design was adopted aimed to identify the perception of faculties and students at the university level towards online learning. Only 119 students and 44 faculties of the Tribhuvan University of Nepal were surveyed based on accidental sampling through the questionnaire. Only 6students and 6 faculties were included in the focus group discussion. The perception of students and faculties was identified through the Likert-type scale and focus group discussion. Faculties have experienced stressful, painful, transformative experiences toward online learning. However, students have experienced effective, enjoyable experiences except for connectivity problems and less interactive environments towards online learning. From the comparative perspective, the perception of faculty members includes the lack of students’ participation in the learning process, inactivity and difficulty to expose on the screen for a long time.